PENGEMBANGAN PERANGKAT PEMBELAJARAN MEKATRONIKA BERBASIS KOMPUTER POKOK BAHASAN PROGRAMMABLE LOGIC CONTROLLER BERORIENTASI PADA PEMBELAJARAN LANGSUNG - Wahyu Dwi Kurniawan; Agung Prijo Budijono (Faculty of Engineering, Universitas Negeri Yogyakarta, 2013)
AbstractProgram Logic Controller is subject that many complaints by students of Department of Mechanical Engineering FT-Unesa. This is due to the lack of learning devices are used so that learning becomes less favorable and become passive. This study aims to develop computer-based learning device mechatronics subject-oriented programmable logic controller directly on student learning Mechanical Engineering Department Unesa FT. This study was conducted in two phases. Phase I, the development of the learning refers to the design of the Model 4D Thiagarajan (1974), Phase II, trial learning in the classroom using a design of one group pretest-posttest design. The findings of the study: (1) an average score of 3.32 learning assessment tools (pretty good), (2) average scores on tests of learning implementation I of 3.59 (good) and trials II of 3.70 (both ), (3) student learning outcomes of cognitive and psychomotor aspects have achieved individually and classical mastery, (4) students showed a positive response to the stated learning tehadap interested, excited, and motivated to attend lectures mechatronics; activity of the most dominant college students are discussin /practices relevant to teaching and learning that is on trial I is 36.46% and trials II 38.19%. Based on the analysis of data, it can be concluded that the developed learning feasible for use in lectures mechatronics. Implementation of the computer-based learning mechatronics subjects PLC can improve the quality of teaching and learning, as students showed a positive response, implementation category learning and learning outcomes both cognitive and psychomotor aspects of students have achieved mastery individually and classical. Keywords: development, learning, mechatronics, computer, plc